Beekeeping Activity Developed by the Beekeepers Association in Cariús-CE (Research, Society and Development, 2020)
The cooperatives and associations are very effective ways to boost the activities including beekeeping, because the collective work provides greater opportunities for all who participate. Beekeeping is in a very important activity for people in the field and thus a source of extra income for these people, causing them to remain on their properties. In the municipality of Carius was no different as beekeeping has emerged as an opportunity for people who mostly depend only on agriculture to survive and saw in beekeeping a source of extra income for their families. Therefore, the aim of this work was to verify the situation of beekeeping developed by the association of beekeepers, seeking relevant information to serve as local development tools. To conduct this research, we chose the city of Carius by the lack of studies of this nature, for both held the collection of primary data from the association of beekeepers, soon after it was made a descriptive analysis of the data, these being represented by means of graphics. Research shows that with the production and marketing of honey, beekeepers can earn a satisfactory monthly income, which comes to a minimum wage. This paper therefore concludes that the activity is able to generate employment and income for beekeepers and that the association has become a key part of this activity and has become an important local development tool.